Analisis Faktor Yang Mempengaruhi Kejadian Fraud Pada Organisasi Perangkat Daerah Kabupaten Manggarai - Yuliani, Priska; Ardini, Lilis; Kurnia, Kurnia (Jurnal Manajerial, 2024)
Background - Fraud is an interesting issue to discuss and it is necessary to study cases that often occur in organizational management areas such as regional apparatus organizations. Some Fraud cases occur in Indonesia due to failures in the accountability process of the government such as failed leadership styles, inappropriate compensation and individual morality. Objective - To examine the effect of leadership style, compensation suitability and individual morality on Fraud in Regional Apparatus Organizations in Manggarai Regency, East Nusa Tenggara (NTT). Design / Methodology / Approach - Using quantitative methods with a questionnaire distributed to 100 employees from 20 OPDs in Manggarai Regency, who are authorized to use the budget as respondents who are eligible to be sampled. The sampling technique in this study used purposive sampling technique with the data analysis method used was path analysis with the sobel test processed by SPSS version 26. Results and Discussion - Individual behavior, leadership style, suitability of compensation, and individual morality have no influence on unethical behavior, while compliance with financial rules influences unethical behavior. Leadership style, suitability of compensation, individual morality and compliance with financial regulations have no effect on the occurrence of Fraud, while internal control has a negative effect on Fraud. Unethical behavior is able to moderate internal control variables, individual morality, and compliance with financial regulations regarding Fraud incidents. Conclusion - The unethical behavior variable can be an intervening variable in the occurrence of Fraud in the Manggarai OPD. The Manggarai Regency Government is expected to be able to prevent Fraud by considering the influencing factors and factors that mediate the occurrence of Fraud. Research limitations - Has several limitations, namely that it was only carried out on 20 OPDs in Manggarai Regency, NTT, so that it cannot be generalized to a wider area.